Assessing the Influence of Glucosamine Supplementation on Synovial Fluid Dynamics in Osteoarthritic Knee Joints - Sadique, Mo; Jaishwal, Kshitendra Mohan; Shah, Sapna Ratan (International Journal of Applied Sciences and Biotechnology, 2024)
Osteoarthritis (OA) is a prevalent joint disorder characterized by the degeneration of articular cartilage, leading to pain, stiffness, and impaired joint function. Synovial fluid plays a crucial role in maintaining joint health by providing lubrication, shock absorption, and nutrient supply to the articular cartilage. In Osteoarthritis, alterations in synovial fluid composition and flow dynamics contribute to disease progression and symptom severity. Glucosamine, a popular dietary supplement, is widely used for its purported benefits in managing Osteoarthritis symptoms and potentially slowing disease progression. Understanding how glucosamine affects synovial fluid dynamics in osteoarthritic knee joints is essential for optimizing treatment strategies and improving patient outcomes. Our research focuses on investigating the impact of glucosamine supplementation on synovial fluid dynamics within the knee joint of individuals with Osteoarthritis. Using computational modeling and simulation techniques, we explore the complex interplay between synovial fluid flow, cartilage health, and glucosamine supplementation. By analyzing synovial fluid flux in both the joint cavity and articular cartilage, we aim to elucidate how glucosamine influences fluid dynamics and joint biomechanics in osteoarthritic knees. Through our computational simulations, we assess the pressure gradient-induced flow of synovial fluid and its variations in response to glucosamine supplementation. Graphical representations of our findings provide insights into the underlying mechanisms driving synovial fluid dynamics and highlight the influence of glucosamine on these processes. By examining the effects of glucosamine on key model parameters, such as synovial fluid viscosity, cartilage integrity, and inflammatory markers, we aim to delineate the mechanisms through which glucosamine may exert its therapeutic effects in Osteoarthritis. Int. J. Appl. Sci. Biotechnol. Vol 12(2): 84-91.